External Stability Under Alternative Nominal Exchange Rate Anchors : An Application to the GCC Countries - Iqbal, Zubair (IMF Working Papers; Working Paper ;, 1997)
Import and export stability is examined under two alternative nominal exchange rate anchors, the U.S. dollar and the SDR. Stability under the two pegs depends critically on import and export elasticity with respect to exchange rates. The implications of import and export elasticity for an optimal currency basket are also explored. The elasticity estimates for the GCC countries suggest that the SDR peg may not outperform the dollar peg in improving external stability. Nevertheless, switching to some other nominal exchange rate anchor may improve external stability, a possibility that remains to be explored.